Electrical conductivity of silicon carbonitride‐reduced graphene oxide composites. Issue 11 (26th June 2017) - Yu, Yuxi; Xia, Fansen; Huang, Qifan; Fang, Jiyu; An, Linan
Abstract: Silicon carbonitride ceramics–reduced graphene oxide (SiCN–rGO) composites are synthesized using polyvinylsilazne (PVSZ) and GO as precursors and N‐dimethylformamide (DMF) as a solvent. We find that the electrical conductivity of SiCN–rGO composites exhibits nonmonotonic changes as a function of GO concentrations, in which the conductivity increases by six orders of magnitude from 7.41E‐09 (Ω/cm) −1 to 4.35E‐03 (Ω/cm) −1 after the integration of 0.2 wt% GO, followed by three orders of magnitude drop to 3.34E‐06 (Ω/cm) −1 when 0.3 wt% GO is integrated. Based on the energy‐dispersive spectroscopy and Raman spectroscopy analysis, we conclude that the conductive behavior of SiCN–rGO composites is controlled by both the concentration and the distribution of "free‐carbon" in the composites.